2019
DOI: 10.1111/jam.14336
|View full text |Cite
|
Sign up to set email alerts
|

Growth optimization, free radical scavenging and antibacterial potential of Chlorella sp. SRD3 extracts against clinical isolates

Abstract: Aim The aim of present work was to explore the potential of Chlorella sp. SRD3 extracts for antioxidant and antibacterial activity along with the evaluation of minimum inhibitory concentration (MIC) and haemolytic activity to detect RBC cell damage. Methods and Results Screening and isolation of microalgae was performed using bold basal medium under normal illuminance (at 27°C) and microscopic observation. Growth of the microalgae was optimized using a different medium and light source. The isolated microalgae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…Extract from Chlorella sp. was very effective as antibacterial agent against S. aureus, E. coli, B. subtilis and B. cereus, which have been noted previously by ( Kellam and Walker, 1989 , Salem et al, 2014 , Santhosh et al, 2019 , Thamilvanan et al, 2016 ). Among genus Scenedesmus , the inhibition effect of ME from S. obliquus was found active against E. coli , B. cereus , and S. aureus with an inhibition zone between 9 and 9.7 mm ( Marrez et al, 2019 ).…”
Section: Discussionsupporting
confidence: 69%
“…Extract from Chlorella sp. was very effective as antibacterial agent against S. aureus, E. coli, B. subtilis and B. cereus, which have been noted previously by ( Kellam and Walker, 1989 , Salem et al, 2014 , Santhosh et al, 2019 , Thamilvanan et al, 2016 ). Among genus Scenedesmus , the inhibition effect of ME from S. obliquus was found active against E. coli , B. cereus , and S. aureus with an inhibition zone between 9 and 9.7 mm ( Marrez et al, 2019 ).…”
Section: Discussionsupporting
confidence: 69%
“…The effect of phenol on the fungi used in the study was recorded by the phenolic methanolic extract, the highest percentage of inhibition against (Candida albicans) was with a diameter of (26) mm, and the least inhibition was against the fungus (Aspergillus niger) with a diameter of (20) mm, and the phenolic hexane extract had the highest inhibition against (Candida albicans) fungus, with a diameter of (26) mm, and the lowest inhibition rate was in (Aspergillus niger), with a diameter of (18) mm. The Inhibition diameters higher than the crude extract of algae indicated that it affected its pure isolated form better than it was mixed with the rest of the materials and components, which reduces its effect and concentration in the concentration used against bacteria, and this result was consistent with a study [25].…”
Section: Resultssupporting
confidence: 89%
“…The combined TPC (the sum of TPC of aqueous and methanolic extracts) in all the species examined (6–12 mg GAE g −1 DW) was in some cases lower [ 53 , 54 , 55 , 56 ], similar [ 8 , 11 , 17 , 48 , 49 , 52 , 56 , 57 ], or higher [ 11 , 14 , 15 , 17 , 48 , 49 , 55 , 58 ] than previously reported values. In practical terms, the phenolic content of 5.1–6.85 mg GAE g −1 DW presented by N. oculata and T. lutea was ten times higher than that of herbs like rosemary, sage, and mint (0.5–0.6 mg GAE g −1 DW) [ 59 ] but lower than that of agri-food waste products like grape vines, tomato waste and grapefruit waste, which have a high phenolic content (32 mg GAE g −1 DW for dried grape vines) and strong antioxidant capacity [ 60 ].…”
Section: Resultsmentioning
confidence: 57%